1962
DOI: 10.1126/science.138.3536.42
|View full text |Cite
|
Sign up to set email alerts
|

Serial Propagation of Influenza B (Lee) Virus in a Transmissible Line of Canine Kidney Cells

Abstract: The serial propagation of influenza B (Lee) virus has been demonstrated in a transmissible line of canine kidney cells, as evidenced by the presence of cytopathic effects and hemagglutinins in each of six consecutive tissue-culture passages, and by egg infectivity titers of 10-4.3 and 10-4.1 per 0.1 ml in 3rd and 5th tissue culture fluids, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1967
1967
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The allantoic sacs of embryonated eggs became an ideal substrate for influenza vaccines because they supported high antigen yields. The vast majority of current influenza vaccines are also produced in eggs from viruses propagated exclusively in eggs because vaccines produced in cell culture systems have not yet been licensed in most countries (22,33,50). Although the egg allantoic sac has been used successfully to produce influenza vaccines for 60 years, recent human H3N2 viruses have largely lost the ability to replicate in this host unless they acquire certain mutations in the HA (48,80).…”
Section: Discussionmentioning
confidence: 99%
“…The allantoic sacs of embryonated eggs became an ideal substrate for influenza vaccines because they supported high antigen yields. The vast majority of current influenza vaccines are also produced in eggs from viruses propagated exclusively in eggs because vaccines produced in cell culture systems have not yet been licensed in most countries (22,33,50). Although the egg allantoic sac has been used successfully to produce influenza vaccines for 60 years, recent human H3N2 viruses have largely lost the ability to replicate in this host unless they acquire certain mutations in the HA (48,80).…”
Section: Discussionmentioning
confidence: 99%
“…They also derived the MDCK cell line from a seemingly normal adult female cocker spaniel but it appears they did not publish isolation of this line. However, MDCK cells were used to study viral infection [17], and subsequently characterised for the first time by Gaush et al in 1966 [1]. Then in the late 1970s/early 1980s the cell line started to become widely used for studying epithelial development and function [18].…”
Section: The Parental Mdck (Nbl-2) Linementioning
confidence: 99%
“…MDCK cells are readily permissive for a wide variety of flu strains [10,11] and lately optimal conditions for growing an influenza vaccine in MDCK cell line cultivated in a serum-free medium were determined [7]. Comparison of egg-to MDCK-grown influenza vaccine showed that the latter induced superior protection of ferrets against subsequent challenge with infectious virus grown in either host cell type [6].…”
Section: Page | 24mentioning
confidence: 99%
“…The original MDCK cell line was established in 1958 by Madin & Darby [9] and a few years later it was recognized that MDCK cells are readily permissive for a wide variety of flu strains [10,11].…”
Section: Introductionmentioning
confidence: 99%